2021
DOI: 10.3389/fpsyg.2021.623873
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Hope Mediate the Relationship Between Gratitude and Depression Among Front-Line Medical Staff During the Pandemic of COVID-19

Abstract: BackgroundThe pandemic of Coronavirus Disease 2019 (COVID-19) has burdened an unprecedented psychological stress on the front-line medical staff, who are at high risk of depression. While existing studies and theories suggest that factors such as gratitude, social support, and hope play a role in the risk of depression, few studies have combined these factors to explore the relationship between them.ObjectiveThis study examined the mediating roles of social support and hope in the relationship between gratitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 45 publications
1
57
1
Order By: Relevance
“…To increase the HCWs' satisfaction rates, their accomplishments at the pandemic were found to be positively associated with higher occupational satisfaction rates [117]. Moreover, as mentioned earlier, the better the performance of communication dimension, including the psychological support, will raise the HCWs' job satisfaction and lower the rates of burnout and stress [110,117]. Some HCWs felt stress and fear mainly due to the possibility of transmitting the virus to their family member and the elderly living in their house [113].…”
Section: The Hcws-centeredness Dimensionmentioning
confidence: 75%
See 1 more Smart Citation
“…To increase the HCWs' satisfaction rates, their accomplishments at the pandemic were found to be positively associated with higher occupational satisfaction rates [117]. Moreover, as mentioned earlier, the better the performance of communication dimension, including the psychological support, will raise the HCWs' job satisfaction and lower the rates of burnout and stress [110,117]. Some HCWs felt stress and fear mainly due to the possibility of transmitting the virus to their family member and the elderly living in their house [113].…”
Section: The Hcws-centeredness Dimensionmentioning
confidence: 75%
“…It found that lower levels of HCW's psychological distress symptoms, burnout, and intentions to quit were perceived when these communication resources were more available. Another study [110] indicated that gratitude in communication could reduce depression in HCWs by promoting social support and hope, respectively.…”
Section: The Responsiveness and Communication Dimension In Covid-19mentioning
confidence: 99%
“…By having such social ties, one may gain access to the resources embedded in these social ties (e.g., advice, assistance, information, ideas, opportunities, power, emotional support, Li et al., 2019 ), and having access to such resources may signal one has a reserve of resources to be drawn on in times of need. This can improve their sense of meaning, sense of purpose and hope ( Feng and Yin, 2021 ), which may ultimately be positive for mental health (cf., Marroquín et al., 2020 ; Thoits, 2011 ). This set of resources to which individuals have access, thanks to their social ties and connections with others, is defined in the existing literature as personal social capital (PSC; King and Lee, 2016 ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Because the COVID-19 pandemic is a community disaster with many unwanted social restrictions, we hypothesised that gratitude might be important in protecting against depression. Although gratitude has been reported to have a positive impact on the mental health of service providers [ 18 ], few studies have investigated its protective effects on depression in the general population during the COVID-19 pandemic. Regular physical exercise can also provide protection against future depression [ 19 ].…”
Section: Introductionmentioning
confidence: 99%